2013
DOI: 10.1007/s00415-013-7161-2
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal stimulation for primary generalised dystonia: effect on cognition, mood and quality of life

Abstract: We investigated the effect of pallidal deep brain stimulation (GPi-DBS) in dystonia on cognition, mood, and quality of life and also assessed if DYT1 gene status influenced cognitive outcome following GPi-DBS. Fourteen patients with primary generalized dystonia (PGD) were assessed, measuring their estimated premorbid and current IQ, memory for words and faces, and working memory, language, executive function, and sustained attention, one month before and one year or more after surgery. Changes in mood and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…Postoperative health‐related QoL assessed by the SF‐36 scale was good and similar to that of the data from the French general population of a similar age . Different results were reported in patients with cervical dystonia treated with botulinum toxin injections, with depression the main predictor of worse QoL, and in patients with isolated generalized dystonia treated by GPi‐DBS with dissociation between motor improvement and impact on QoL …”
Section: Discussionmentioning
confidence: 99%
“…Postoperative health‐related QoL assessed by the SF‐36 scale was good and similar to that of the data from the French general population of a similar age . Different results were reported in patients with cervical dystonia treated with botulinum toxin injections, with depression the main predictor of worse QoL, and in patients with isolated generalized dystonia treated by GPi‐DBS with dissociation between motor improvement and impact on QoL …”
Section: Discussionmentioning
confidence: 99%
“…Another reason is that patients with major and active psychiatric issues have frequently been excluded from studies examining long-term postoperative outcomes with reported results being mostly limited to patients without major psychiatric difficulties before surgery. [13][14][15][16][17][18][19] However, 3 suicides have been reported so far within 14 months after bilateral GPi DBS. 20,21 Moreover, studies reporting neuropsychiatric outcomes in various types of dystonia (primary generalized, cervical, and secondary dystonia) and in the long-term follow-up are lacking.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…Therefore, the neuropsychiatric consequences of GPi DBS on patients with dystonia in the short and long term remain unclear, as does the influence of active psychiatric disorders on the selection of appropriate candidates for the procedure. [12][13][14][15][16][17][18][19][20][21][22] We report the long-term impact of bilateral GPi DBS on the neuropsychiatric profiles of a population of patients with primary and secondary dystonia, assessed with the Structured Clinical Interview for the DSM-IV Axis I psychiatric disorders (SCID-I). 23 METHODS Primary research question.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…Comparison with healthy controls found MC and NMC cases to have reduced motor sequence (p < 0.05) and visual sequence (p < 0.05) learning, while executive function scores in the MC cases were significantly lower from that of controls (p ¼ 0.022). Finally, comparison of DYT1 MC and an equal number of DYT1 negative generalized dystonia cases postdeep brain stimulation (DBS) found no differences in either postoperative cognitive function or psychiatric state [6].…”
Section: Dyt1mentioning
confidence: 99%